2000
DOI: 10.1007/s001250051327
|View full text |Cite
|
Sign up to set email alerts
|

Serine residues 994 and 1023/25 are important for insulin receptor kinase inhibition by protein kinase C isoforms β2 and θ

Abstract: The tyrosine kinase activity of the human insulin receptor (HIR) is essential for its signalling function [1]. Insulin-induced autophosphorylation of the receptor b-subunit at tyrosine residues in the kinase domain and in the juxtamembrane domain of the receptor b-subunit is critical for autoactivation of the receptor and for substrate phosphorylation [2,3]. After the rapid insulin-stimulated tyrosine phosphorylation of the receptor b-subunit, there is a delayed insulinstimulated increase of serine and threoni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 39 publications
2
36
0
1
Order By: Relevance
“…Serine phosphorylation sites have been mapped to several residues including S 307 , S 312 , and S 616 in human IRS-1 (23,(41)(42)(43); insulin resistance has been linked to serine phosphorylation of IRS-1. Our finding that BVR phosphorylates synthetic IRS-1 peptides specifically lacking tyrosine, but otherwise identical to IRS-1 peptides used as IRK substrates, indicates that IRS-1 is a likely substrate for BVR serine͞threonine kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Serine phosphorylation sites have been mapped to several residues including S 307 , S 312 , and S 616 in human IRS-1 (23,(41)(42)(43); insulin resistance has been linked to serine phosphorylation of IRS-1. Our finding that BVR phosphorylates synthetic IRS-1 peptides specifically lacking tyrosine, but otherwise identical to IRS-1 peptides used as IRK substrates, indicates that IRS-1 is a likely substrate for BVR serine͞threonine kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that activated PKC isoform(s) impairs insulin signalling by increasing the phosphorylation of insulin receptor susbtrates (IRS)-1/2 at serine/threonine residues. Indeed, PKC isoform(s) attenuates insulin signalling by IRS-1 phosphorylation at serine/threonine residues (Chin et al 1994, Bossenmaier et al 1997, De Fea & Roth 1997, Strack et al 2000. Therefore, activation of PKC isoform(s) might be an important negative regulator of insulin receptor function.…”
Section: Discussionmentioning
confidence: 99%
“…As a serine-threonine kinase, PKCδ might be expected to function primarily as a negative regulator of IR signaling, particularly in view of the role of serine phosphorylation on activities of IR and IRS [103][104][105]. And, indeed, many studies have shown that activated PKCδ readily serine phosphorylates these important proteins.…”
Section: Novel Pkc Isoforms Pkcδmentioning
confidence: 99%